Effective communication in the nurse-patient relationship in the light of Transcultural Interprofessional Practice model - Josefa Fernanda Evangelista de Lacerda; Paula Suene Pereira dos Santos; Evanira Rodrigues Maia; Dayanne Rakelly de Oliveira; Maria Corina Amaral Viana; Edilma Gomes Rocha Cavalcante (Universidade Federal do Ceará, 2021)
Objective: to analyze the use of elements of effective nurse-patient communication in the light of the Transcultural Interprofessional Practice model. Methods: an integrative literature review was carried out in the CINAHL, LILACS, MEDLINE, SCOPUS, and Web of Science databases, without a time limit. Results: 12 studies were analyzed, most of them published in the English language, in 2017. Two categories were elaborated: effective verbal and non-verbal communication between nurses and patients. The elements of effective verbal communication were presented as speech and language; non-verbal ones presented as signals, distance, eye contact, time, touch, listening, empathy, and patience. Technology-assisted communication was part of both. Less frequently, the verbal communication process was hindered by language and non-verbal communication due to a lack of time availability. Conclusion: effective communication favors the establishment of trust, interaction, and the nurse-patient relationship.